Electrokinetic Separation of Heavy Metals from Wastewater Treatment Sludge - Park, Seon-Young; Park, Geun-Yong; Kim, Do-Hyung; Yang, Jung-Seok; Baek, Kitae (TAYLOR & FRANCIS INC, 2010)
In the study, a preliminary experiment on the removal of heavy metals from industrial wastewater sludge was carried out to evaluate the feasibility of electrokinetic separation. Four different types of processing fluidtap water, ethylenediaminetetraacetic acid (EDTA), citric acid (CA), and 0.1M nitric acidwere tested. EDTA was found to be the most effective agent within the set of chemicals tested for removing heavy metals from sludge because of its strong chelating ability with metals. The removal efficiency of Pb and Cu was higher than that of Zn and Ni for all fluids. In tap water, EDTA, and CA, the metals moved toward the anode, implying that they existed as complexes with EDTA and CA or organic matter in the processing fluid. In nitric acid, the metals moved toward the cathode because nitric acid effectively desorbed the metal from the sludge; however, the removal efficiency was very low. The results indicated that electrokinetic technology effectively separated Cu and Pb, but not Zn and Ni.